Women with HIV presenting at three London clinics between 1985-1992. Issue 6 (December 1993) - Shah, P N; Iatrakis, G M; Smith, J R; Wells, C; Barton, S E; Kitchen, V S; Kourounis, G; Steer, P J
Abstract : OBJECTIVE–To determine the changing patterns of HIV infection in women in three units in London. SUBJECTS–Three hundred and fifty seven HIV seropositive women who have attended outpatient clinics between 1984 and 1992. METHODS–A retrospective review of data obtained from a computerised database and supplemented by direct inspection of the notes. RESULTS–The number of newly identified women with HIV has risen steadily over the period of study with a significant shift towards a heterosexual mode of transmission. This is a reflection of increasing numbers of women from Sub-Saharan Africa rather than a rise in the incidence of HIV in women born in the UK. CONCLUSIONS–The increase in women infected by HIV remains predominantly restricted to women in "high risk" groups. Although encouraging, our data should be interpreted with caution since it suffers from the inherent bias of selective testing. Safer sex education and epidemiological surveillance should continue despite the apparent low risk to women born in the UK.